Thermal and Petrographic Characterization of Herculaneum Wall Plasters. (17th November 2016) - Leone, G.; De Vita, A.; Magnani, A.; Rossi, C.
Abstract : Roman plasters sampled from different houses at the archaeological site of Herculaneum, Italy, (2010–12) were studied by means of petrography, thermal analysis and X‐ray fluorescence. Herculaneum plasters are composed by preparatory layers (arriccio) with a thickness of several centimetres and are based on a calcitic binder and volcanic scoriae as aggregates, covered by a thin final layer characterized by a low granulometry. Most of the sampled plasters can be placed into two groups based on the aggregate composition and classified as marmorino or intonachino. However, a similar aggregate composition did not induce superimposable thermal behaviour, thus suggesting that the samples underwent different ageing/weathering processes, with a consequent change of the ratio among the components.